NEURO-ENDOCRINE-IMMUNE MODULATION BY AYURVEDIC RASAYANA DRUGS (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda which literally means “the science of life” is the ancient Indian system of medicine. Rasayana is a specialized branch of Ayurveda. The drugs attributed with Rasayana properties are mentioned to delay the process of ageing, enhance the mental and cognitive functions and deliver freedom from a number of diseases including those caused by infectious organisms. All these activities of Rasayana drugs seem to be associated with neuro-endocrine-immune systems. In this study we have reviewed the growing inter-relationship between the neuro-endocrine-immune systems and stress as a neuro-endocrine-immune phenomenon. Some important Ayurvedic Rasayana drugs including Aswagandha (Withania somnifera), Tulsi (Ocimum sanctum), Guduchi (Tinospora cordifolia), Shilajit (Asphalt), Brahmi (Bacopa monnieri) and few others along with their pharmacological actions on the above three systems and stress as well have also been reviewed. It has been observed that most of them tend to exhibit their activities by modulating the neuro-endocrine-immune systems along with anti-stress/adaptogenic capability. The scientific inter-relationship between the three systems has been taken as the model reference. Similar actions are expected from other Rasayana drugs too. Therefore Rasayana drugs in Ayurveda can be evaluated and used as neuro-endocrine-immune modulators.